Use of fluorescence microscopy to study intracellular signaling in bacteria - Kentner, David; Sourjik, Victor (Annual review of microbiology, 2010)
Following the introduction of fluorescent protein tags, the application of fluorescence microscopy in microbial cell biology has advanced the field dramatically. We now understand that bacterial cells are not simple bags of enzymes but have complex internal structures, and that specific intracellular organization plays an important role in a number of processes, including signal transduction. The quantitative nature and high temporal resolution of fluorescence microscopy make it particularly useful for studies of intracellular dynamic systems, such as signaling networks. Applications of fluorescence microscopy in signaling are not limited to studying localization. Several techniques allow researchers to follow real-time dynamics of protein interactions, at steady state or upon stimulation, and therefore to investigate signal propagation, amplification, and integration in the cell. Moreover, microscopy enables investigation of single-cell gene expression kinetics, bringing such concepts as cell individuality and robustness against stochasticity of gene expression to the forefront of signaling studies.